PENGARUH ROI, ROE, DAN NPM TERHADAP HARGA SAHAM PERUSAHAAN JASA SEKTOR TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2020: Return on Investment, Return on Equity, Net Profit Margin - Niswan Bayu Syasindy; Muhammad Ali Machrus (Jurnal Penelitian Multidisiplin, 2022)
This research focuses on the nominal movement of stock prices based on the calculation of profitability ratios consisting of Return on Investment (ROI), Return on Equity (ROE), and Net Profit Margin (NPM) in transportation and logistics service companies listed on the Indonesia Stock Exchange (IDX) period 2017-2020. The data analysis method used descriptive statistics, classical assumption test (multicollinearity test, heteroscedasticity test, autocorrelation test, and data normality test), multiple linear regression analysis, hypothesis testing (simultaneous test and partial test), and the coefficient of determination test using statistical aids in the form of SPSS application. The results obtained in this research are the variables Return on Investment (ROI), Return on Equity (ROE), and Net Profit Margin (NPM) partially have no effect on stock prices. Meanwhile, simultaneously the Return on Investment (ROI) variables, Return on Equity (ROE), and Net Profit Margin (NPM) have a positive influence on changes in stock prices.